Products Derived from Buchenavia tetraphylla Leaves Have In Vitro Antioxidant Activity and Protect Tenebrio molitor Larvae against Escherichia coli-Induced Injury - Tiago Fonseca Silva; José Robson Neves Cavalcanti Filho; Mariana Mirelle Lima Barreto Fonsêca; Natalia Medeiros dos Santos; Ana Carolina Barbosa da Silva; Adrielle Zagmignan; Afonso Gomes Abreu; Ana Paula Sant'Anna da Silva; Vera Lúcia de Menezes Lima; Nicácio Henrique da Silva; Lívia Macedo Dutra; Jackson Roberto Guedes da Silva Almeida; et al. (MDPI AG, 2020)
The relevance of oxidative stress in the pathogenesis of several diseases (including inflammatory disorders) has traditionally led to the search for new sources of antioxidant compounds. In this work, we report the selection of fractions with high antioxidant action from B. tetraphylla (BT) leaf extracts. In vitro methods (DPPH and ABTS assays; determination of phenolic and flavonoid contents) were used to select products derived from B. tetraphylla with high antioxidant action. Then, the samples with the highest potentials were evaluated in a model of injury based on the inoculation of a lethal dose of heat-inactivated Escherichia coli in Tenebrio molitor larvae. Due to its higher antioxidant properties, the methanolic extract (BTME) was chosen to be fractionated using Sephadex LH-20 column-based chromatography. Two fractions from BTME (BTFC and BTFD) were the most active fractions. Pre-treatment with these fractions protected larvae of T. molitor from the stress induced by inoculation of heat-inactivated E. coli. Similarly, BTFC and BTFD increased the lifespan of larvae infected with a lethal dose of enteroaggregative E. coli 042. NMR data indicated the presence of aliphatic compounds (terpenes, fatty acids, carbohydrates) and aromatic compounds (phenolic compounds). These findings suggested that products derived from B. tetraphylla leaves are promising candidates for the development of antioxidant and anti-infective agents able to treat oxidative-related dysfunctions.